Scaffolds with controlled release of pro-mineralization exosomes to promote craniofacial bone healing without cell transplantation. (December 2020) - Swanson, W. Benton; Zhang, Zhen; Xiu, Kemao; Gong, Ting; Eberle, Miranda; Wang, Ziqi; Ma, Peter X.
Abstract: Biomimetic bone regeneration methods which demonstrate both clinical and manufacturing feasibility, as alternatives to autogenic or allogenic bone grafting, remain a challenge to the field of tissue engineering. Here, we report the pro-osteogenic capacity of exosomes derived from human dental pulp stem cells (hDPSCs) to facilitate bone marrow stromal cell (BMSC) differentiation and mineralization. To support their delivery, we engineered a biodegradable polymer delivery platform to improve the encapsulation and the controlled release of exosomes on a tunable time scale from poly(lactic-co-glycolic acid) (PLGA) and poly(ethylene glycol) (PEG) triblock copolymer microspheres. Our delivery platform integrates within three-dimensional tissue engineering scaffolds to enable a straightforward surgical insertion into a mouse calvarial defect. We demonstrate the osteogenic potential of these functional constructs in vitro and in vivo . Controlled release of osteogenic hDPSC-derived exosomes facilitates osteogenic differentiation of BMSCs, leading to mineralization to a degree which is comparable to exogenous administration of the same exosomes in human and mouse BMSCs. By recruiting endogenous cells to the defects and facilitating their differentiation, the controlled release of osteogenic exosomes from a tissue engineering scaffold demonstrates accelerated bone healing in vivo at 8 weeks. Exosomes recapitulate the advantageous properties of mesenchymal stem/progenitor cells, without manufacturing or immunogenic concerns associated with transplantation of exogenous cells. This biomaterial platform enables exosome-mediated bone regeneration in an efficacious and clinically relevant way. Graphical abstract: Image, graphical abstract